(3cTa GdbfGY aj QSe GdCQHGYs - (3eMeO Hf eMeO Hf eMeO GdHcQj GdTGaYj, CHh YHO Gddg,J (B840 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLg (B: (3agPg OjHGLg dWjag SjeJgG HcTa GdbfGY ai QSe GdCQHGY hPcQJ ajgG GdeSJYed ZGdHkG NeSkG hYTQjf BdI ef PhGJ GdChVGY GSJaOJgG ef GdeTGjN hGdBdGJ HGdcTa hGdGWdGY s
(3BNQgG (B:s
(3de JCJ ajg EdG HGdCUhd Ch HBdGJ ZQjHgI hcd Pdc ef ahGFO TjNfG GdCSJGP GdYdGeg GdaGVd fhQ GdOjf GdfbGT YHO GdbGOQ ai Sfg KdGKjf hKeGfeGFg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B273s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B127 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B85 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1494s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjg (B((3ejbGJ (B124) s
Keywords: (3Gdadcs